Some Quality Parameters of Intermediate Moisture, Deep-Fried Mackerel (Scomberomorus commersoni, Lacepede) - Che Man, Yaakob; Atan, Maznah (1984)
Intermediate Moisture Deep-fried Mackerel seasoned with local ingredients was prepared by infusion method from an aqueous solution containing PEG 200, sorbic acid and BHA. The products were deep-fried at 190°C for 3 and 4 minutes, resulting in water activity (aw) of 0.84 and 0.80 respectively. Tests on chemical, physical and organoleptic properties were carried out. The Intermediate Moisutre Deepfried Mackerel was found to be generallv acceptable.